SI APIK Application User Satisfaction with The TAM and Delone and Mclean Approach: An Empirical Study on Micro, Small and Medium Enterprises (MSME) in Banda Aceh - Yulia Rahmana; Mirna Indriani (UNIB Press, 2022)
The research objective was to see the effect of the information system quality, information quality, perceived usefulness, and perceived ease of use on user satisfaction of the SI APIK application. The study population was Micro, Small, and Medium Enterprise (MSME) that had attended training on compiling Android-based financial reports. The study sample that included 32 respondents were determined using the census method. The sample collection was carried out by means of a questionnaire to the respondents. The results showed that quality of information systems has no significant effect on user satisfaction of SI APIK application, quality information has no significant effect on user satisfaction of SI APIK application, perceived usefulness is significant on user satisfaction of SI APIK application, perceived ease of use has no significant effect on user satisfaction of SI APIK application, quality of information systems, quality information, perceived usefulness, and perceived ease of use simultaneously affect user satisfaction of SI APIK application